Mesoporous silica containing sulfonic acid groups as catalysts for alpha-pinene methoxylation - Castanheiro, J (2008)
The methoxylation of a-pinene was studied over sulfonic acid-functionalized mesoporous silica (MCM-41, PMO) at 60ºC. The support functionalization was achieved by the introduction of 3-(mercaptopropyl)trimethoxysilane onto the surface of these materials either by grafting or by co-condensation. The thiol groups were oxidized to SO3H by treatment with H2O2. All the catalysts were active in the studied reaction being the PMO-SO3H-g the best one. Good values of selectivity to a-terpinyl methyl ether were obtained with these catalysts. Catalytic stability of the PMO-SO3H-g was evaluated by performing consecutive batch runs with the same catalyst sample. After the third batch it was observed a stabilisation of the activity.